Structural and electrical properties of infinite-layer CaCuO2 under high pressure - X.M. Qin, Q.Q. Liu, Y. Yu, Z.X. Bao, F.Y. Li, R.C Yu, J. Liu and C.Q. Jin (Science and Technology of Advanced Materials, 2005)
The structural and electrical properties of infinite-layer CaCuO2 (IL CaCuO2) under high pressure at room temperature were studied using a diamond anvil cell by in situ high pressure energy-dispersive X-ray diffraction with synchrotron radiation and by simultaneous resistance and electrical capacitance measurements. The results indicate that the primary crystal structure of IL CaCuO2 is stable under pressure up to 30 GPa with an anisotropic compressibility. The equation of state of IL CaCuO2 was obtained from the V/V0−P relationship based on the Birch–Murnaghan equation, which gives rise to a bulk modulus B0=96 GPa in the low pressure range below 6 GPa, and B0=186 GPa at pressures from 6 to 30 GPa for IL CaCuO2. The resistance and capacitance measurements of IL CaCuO2 up to 20 GPa revealed several unusual changes. There is an abrupt resistance drop in the pressure range of 3–6 GPa followed by an abnormal hump occurring around 12 GPa with increasing pressure. Corresponding changes were also observed in the dependence of capacitance on pressure. The former drop is attributed to an isostructural phase transition as observed in the synchrotron radiation experiments. The latter is considered to be related to an electronic structure transition resulting from the anisotropic compression of the IL CaCuO2 unit cell under high pressure.